2008
DOI: 10.1530/eje-08-0334
|View full text |Cite
|
Sign up to set email alerts
|

Diet or exercise: what is more effective in preventing or reducing metabolic alterations?

Abstract: Objective/design: The influence of diet and exercise on metabolic syndrome is controversial since fit individuals might also eat healthier foods. We evaluated the association of diet/exercise variation with reductions in metabolic variables and C-reactive protein (CRP) values in the experimental and control arms of a 1-year randomized lifestyle intervention trial performed in patients with multiple metabolic abnormalities. Methods: A prospective study of 169 cases and 166 controls after a lifestyle interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
1
30
0
2
Order By: Relevance
“…In the intervention study of Bo et al [33] (LOE Ic), a positive association between SFA intake and weight gain was observed. In the cohort study of Butte et al [31] (LOE IIb), however, it was not.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
“…In the intervention study of Bo et al [33] (LOE Ic), a positive association between SFA intake and weight gain was observed. In the cohort study of Butte et al [31] (LOE IIb), however, it was not.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
“…Accordingly, high blood pressure and impaired glucose metabolism make the early detection of subjects with a very high risk of developing MS possible, allowing them to be prioritised for making the necessary lifestyle changes for both these components and for the later appearance of obesity and dyslipidaemia. Physical exercise [34,35] and changes in diet [36] have been shown to not only reduce the components of MS, but also to prevent its occurrence. This same reasoning may also explain why subjects' triglycerides may experience a substantial change, even though their HDL levels remain stable during the study follow-up period because these participants may have already adjusted their habits towards healthier lifestyles by increasing physical activity and/or changing their diet.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although most feeding trials suggest postprandial elevation in CRP following an SFA-rich meal, postprandial changes in other inflammatory markers such as IL-6 and tumor necrosis factor-alpha (TNFα) are largely inconsistent [29–32]. In cohort studies using dietary assessment, even the association between SFA intake and CRP has yet to be established, with results ranging from null [33], borderline positive [34], to significant in males only [35]. At least one study has applied both semi-quantitative FFQs and plasma lipid FA measurements [36].…”
Section: Discussionmentioning
confidence: 99%